SEJARAH EKONOMI ORANG KALANG DI CILACAP DAN KEBUMEN, 1950an-1990an - , PRADITA DEVIS DUKARNO; , Prof. Dr. Bambang Purwanto, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The focus of this research is about the economic history success and decline of Kalang people as a merchant and businessman in Cilacap and Kebumen, process is described through the economic, social, and cultural aspects. This research uses historical method and also utilizes primary sources, secondary and oral history. The primary sources are photos, marriage certificates and the documents of Kalang people organization. Furthermore, the secondary sources are books and research reports and the oral sources are the relatives of Kalang people and the member of Kalang organization. Moreover, the scope of this research is the period between 1950s-1990s, which based on the consideration 1950s-1970s in the economic of Kalang has success. All of this reason due to considers the period between 1980s-1990s the economic of Kalang people has declined. Historiographically, also this research gives contribution about orang Kalangâs economic which is the study of this theme still a few was done by historian. In trade, Kalang people not only depend on economic factors but also social and cultural aspects. In the social aspect, Kalang people in society is seen as rich people and some of them have worked as village chief so that they are considered as respectable group. In cultural aspect, the identity and kinship of Kalang people, almost them have become as merchants. They always training their children since childhood as merchant. The experience as a merchant since their children have formed and encouraged them to become a merchant. Culturally, in kinship Kalang people are doing marriage between relatives. This marriage can make the wealth of Kalang people doesnât asunder. When the economics of them have fallen, this condition also gives a contribution in social and cultural aspect. In social aspect, Kalang people has recognized as common people. In cultural aspect, many Kalang people become civil servants or work in private area and married with non-kalang people.